Comparing digital public service innovation in urban and rural space: evidence from Indonesia public service innovation competition 2014-2023 - M. Rizki Pratama; Safarudin Hisyam Tualeka (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
This study examines the landscape of digital public service innovation in Indonesia, focusing on a comparison of developments in urban and rural local governments from 2014 to 2023. Using a comparative approach integrated with a systematic search strategy guided by the PRISMA flowchart, this study analyzed 990 documents from the Ministry of Administrative and Bureaucratic Reform's innovation competition, with 170 documents meeting the inclusion criteria based on the title and description of digital public service innovations and the level of government for in-depth content analysis. Findings reveal distinct patterns in digital public service innovation. Local governments show a stronger emphasis on interactive rather than static services, enhancing user engagement, while district governments demonstrate a gradual but growing shift toward interactive solutions. External innovations outnumber internal ones, indicating a priority on citizen-oriented services, yet raising concerns about institutional digital capacity. Furthermore, independent innovation dominates over collaborative efforts, reflecting a lack of cross-sector collaboration in digital governance. This finding highlights the need for a balanced approach that integrates interactivity with accessibility, strengthens internal digital capacity, and encourages collaborative innovation. The study is limited by its reliance on secondary competition data, which may overlook informal initiatives, as well as interpretive bias in document-based categorization. It also does not analyze causal mechanisms such as leadership or bureaucratic culture, and its focus on Indonesia limits its generalizability. Future research should employ qualitative and cross-country comparative methods to deepen and broaden the findings.